Mutations in the Plasmodium falciparum cytochrome b gene are associated with delayed parasite recrudescence in malaria patients treated with atovaquone-proguanil - Fivelman Quinton L; Burke Martina; Price Nicholas; Laundy Matt; Sutherland Colin J; Pasvol Geoffrey; Klein John L; Chiodini Peter L (Malaria Journal, 2008)
Abstract Background Fixed-dose combination antimalarial drugs have played an increasingly important role in the treatment and chemoprophylaxis of falciparum malaria since the worldwide failure of monotherapy with chloroquine. Atovaquone-proguanil is one such combination drug used both for prophylaxis in travellers, and for treatment of acute malaria cases in European hospitals and clinics. Methods A series of eight atovaquone-proguanil treatment failures and two prophylaxis breakthroughs from four UK hospitals from 2004–2008 were analysed for evidence of mutations in the pfcyt-b gene, previously found to be associated with failure of the atovaquone component. Results Parasites carrying pfcyt-b mutations were found in five falciparum malaria patients with recrudescent parasitaemia occurring weeks after apparently successful treatment of a primary infection with atovaquone-proguanil. Four of these cases carried parasites with the Tyr268Cys mutation in pfcyt-b , previously reported in two French patients with malaria. In contrast, mutations in pfcyt-b were not found in three patients treated with atovaquone-proguanil who exhibited delayed clearance of the primary infection, nor in two returning travellers with malaria who had used the combination for prophylaxis. Using current and previously published data, mean time to recrudescence of parasites carrying pfcytb codon 268 mutations was estimated as 28.0 days after treatment (95% C.I. 23.0 – 33.0 days), whereas treatment failures without codon 268 mutations received rescue treatment an average of 4.71 days after initial AP treatment (95% C.I. 1.76 – 7.67 days). Conclusion Genetically-determined parasite resistance to atovaquone is associated with delayed recrudescence of resistant parasites three weeks or more after initial clearance of parasitaemia by atovaquone/proguanil therapy. The 268-Cys allele of pfcyt-b may have been overlooked in previous studies of atovaquone-proguanil treatment failure as it is not detected by current RFLP methods.